(untitled) (Uzbek Scholar Journal, 2022)
Axial deformities of the knee joints in children are a common problem and a frequent reason for contacting an orthopedic doctor [1]. Most of them are physiological, although there are also pathological forms that require timely diagnosis and treatment. The causes of these deformities, indications, terms and methods of their treatment still remain topical issues that need to be addressed. The purpose of this publication is to analyze the literature and present current ideas about axial deformities of the knee joint in children and the possibilities of their correction using the controlled growth method. The formation of the lower limb axis in children goes through a number of stages, manifesting itself in the process of growth by its regular change. In most cases, these deformities are physiological in nature and do not require correction. Thus, a child at birth has a varus deviation of the mechanical axis at the level of the knee joints (the anatomical femoral-tibial angle is 10-15°). According to several authors, this is due to the intrauterine position of the fetus during pregnancy.